2021
DOI: 10.3389/fmed.2021.661359
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Variations in Host Predisposition to COVID-19 Related Anosmia, Ageusia, and Neurological Syndromes

Abstract: The novel coronavirus disease (COVID-19), has become the most critical global health challenge in recent history. With SARS-CoV-2 infection, there was an unexpectedly high and specific prevalence of olfactory and taste disorders (OTDs). These high rates of hyposmia and hypogeusia, initially reported as up to 89% in European case series, led to the global inclusion of loss of taste and/or smell as a distinctive feature of COVID-19. However, there is emerging evidence that there are striking differences in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 134 publications
(112 reference statements)
0
18
0
Order By: Relevance
“…While some studies suggest self-reports may underestimate smell loss prevalence relative to direct assessment 18,30,31 , others found correlations between self-reporting and direct assessments 32 . Furthermore, although direct assessments have been proposed very recently 33 , self-report remains the current standard of care for assessment of parosmia and phantosmia 34 , at least until newly proposed methods can be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies suggest self-reports may underestimate smell loss prevalence relative to direct assessment 18,30,31 , others found correlations between self-reporting and direct assessments 32 . Furthermore, although direct assessments have been proposed very recently 33 , self-report remains the current standard of care for assessment of parosmia and phantosmia 34 , at least until newly proposed methods can be further validated.…”
Section: Discussionmentioning
confidence: 99%
“…This is unlikely to be a decisive factor for two reasons. Careful analyses of East Asians for chemosensory dysfunction revealed low prevalence, 5,89,90 even with objective olfactory testing, 91 and when the olfactory dysfunction was reexamined in Chinese populations at a later date, the anosmia prevalence still was significantly lower in Chinese patients than in Caucasian patients. 92 Second, we show here for South Asians that even studies conducted later in the pandemic, when the media had widely publicized and revealed anosmia/hyposmia as a cardinal symptom of COVID-19, reported a low prevalence when they examined cohorts in a region (e.g.…”
Section: Effects Of Response Bias Age Disease Severity Gender and Methodologymentioning
confidence: 99%
“…3,4,10,114,115 An emerging consensus favors a crucial role of the sustentacular support cells in the olfactory epithelium as the primary mechanism of COVID-induced anosmia. 5,8,114,[116][117][118][119][120] Since the SARS-CoV-2 entry protein (ACE2) is not or only minimally expressed in olfactory receptor neurons, the virus rarely infects the neurons, 121 but rather enters the olfactory epithelium through sustentacular support cells and secretory cells in Bowman glands and primarily damages these cell types (Fig. 5A).…”
Section: Why Does Sars-cov-2 Cause Much More Anosmia Than Sars-cov-1?mentioning
confidence: 99%
See 2 more Smart Citations